2019
DOI: 10.4236/ojst.2019.93008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermocycle Aging on Color Stability of Monolithic Zirconia

Abstract: Background: The color stability of dental restorative materials is important for long-term clinical success. Objectives: The objective of this study was to examine the effect of thermocycling on the color and translucency stability of monolithic zirconia. Materials and methods: A total of 80 disc-shaped specimens (1 cm diameter) were produced from monolithic zirconia material, Katana High Translucent (Kuraray Noritake Dental, Kurashiki, Japan). The specimens were prepared in four different thicknesses: 0.5 mm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Overall, the values of TP ranged from 18.82 and 14.20 for zirconia at TP (T1) and for Mark II at T3, respectively; these values coincided with those publications recorded for the materials used for inlays and veneer ceramic materials [17][18][19][22][23]. The ΔE 00 values at different time intervals were within the clinically acceptable range reported by previous studies [17][18]22,24].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Overall, the values of TP ranged from 18.82 and 14.20 for zirconia at TP (T1) and for Mark II at T3, respectively; these values coincided with those publications recorded for the materials used for inlays and veneer ceramic materials [17][18][19][22][23]. The ΔE 00 values at different time intervals were within the clinically acceptable range reported by previous studies [17][18]22,24].…”
Section: Discussionsupporting
confidence: 87%
“…Those values can be considered acceptable because many recent and previous studies have reported the same values [18,[22][23]. Other works have recorded TP values of 15.00-22.00 for zirconia samples and 13.00-18.00 for feldspathic ceramic CAD/CAM materials after 2 weeks of immersion in khat extract [19]. The reduction in TP values coincided with that reported by Şişmanoğlu and Gürcan 2021, who tested the TP of feldspathic ceramic after immersion in coffee for a period of time and found a slight reduction in the TP values of zirconia samples and feldspathic CAD/CAM ceramic materials after staining [26].…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations